A study on customers' expectations towards ‘energy’; design, price or quality? / Intan Shafinaz Ahmad - Ahmad, Intan Shafinaz (1996)
Today's consumers have changed in terms of lifestyle and priorities. The rise in consumer income as well change their taste and expectations whereby they demand for differentiation on products they purchased. The development of private label program by most of the retailers in their stores is one of the retail strategies to respond to these changes and at the same time meets the customer's expectation. ENERGY is the Mun Loong- Hankyu Jaya brand that offers a unisex apparel which targeted to young people. One research has been conducted to gain the customer's feedback towards the ENERGY. The study was conducted at the ENERGY counter itself in order to have a better understanding of consumer behaviour. Some observation, interviews and distribution of questionnaire were conducted to gather data about customers; to identify whether they were design oriented, price oriented or quality oriented people. The result of the study indicates that majority of the customers were design oriented rather than price and quality oriented.